2016
DOI: 10.1017/s0022149x15001066
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic bacteria of helminths: what role may they play in ecosystems under anthropogenic stress?

Abstract: Symbiotic bacteria are a common feature of many animals, particularly invertebrates, from both aquatic and terrestrial habitats. These bacteria have increasingly been recognized as performing an important role in maintaining invertebrate health. Both ecto- and endoparasitic helminths have also been found to harbour a range of bacterial species which provide a similar function. The part symbiotic bacteria play in sustaining homeostasis of free-living invertebrates exposed to anthropogenic pressure (climate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 100 publications
(178 reference statements)
0
10
0
Order By: Relevance
“…Bacteria have been found in the tegument and gastrodermis of digeneans (LoVerde et al 1980; Gobert et al 2022) and tapeworms (see Morley 2016). For example, Salmonella typhimurium replicate within the S. mansoni tegument where they are protected from antibiotics.…”
Section: The Parasite Lensmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria have been found in the tegument and gastrodermis of digeneans (LoVerde et al 1980; Gobert et al 2022) and tapeworms (see Morley 2016). For example, Salmonella typhimurium replicate within the S. mansoni tegument where they are protected from antibiotics.…”
Section: The Parasite Lensmentioning
confidence: 99%
“…Adult Fasciola hepatica in sheep have a novel Neorickettsia bacteria that is found in reproductive tissues and in mature eggs within the host liver, raising the possibility that this bacterium may be vertically transmitted within Fasciola (McNulty et al 2017). In tapeworms, the abundance and density of bacteria in the tegument depend on the life history of freshwater fish hosts, season, and location within the host intestine (Morley 2016). It was recently shown that the intestinal microbiome of Ascaris lumbricoides has a predominance of Firmicutes and Proteobacteria Phyla and is enriched with Streptococcus in heavily infected hosts, but with Lactococcus in lightly infected hosts (Klomkliew et al 2022).…”
Section: The Parasite Lensmentioning
confidence: 99%
“…For example, the composition of the human microbiome has been linked to gut health, immunity modulation and disease susceptibility (Wang et al, 2017;Fassarella et al, 2021); the taste of wine has been linked to microbial communities in the soil (Belda et al, 2017); and in conservation programmes, the health status of captivity-bred species has been linked to differences in the microbiome composition between their natural and artificial habitats (West et al, 2019). Similarly, symbiotic microbes are also present in helminth parasites and their parasitized hosts, performing central roles in what was previously seen as a two-player interaction (parasitehost), with eco-evolutionary implications for all players involved (Morley, 2016;Dheilly et al, 2019b;Jenkins et al, 2019;Brealey et al, 2022;Hahn et al, 2022;Poulin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Ectosymbiotic bacteria are widely described on the helminths' tegument surface, particularly those worms residing within the host intestinal tract. Other bacteria that present in helminth organs are called endosymbiotic bacteria (Morley 2016). Many factors can affect or alter the relationship between bacteria and parasites, for example, competition for food resources (Ezenwa 2004), secretion of bacterial growth inhibitors by some species (Hewitson et al 2011;Ditgen et al 2014), and host age and diet (Berrilli et al 2012;Glendinning et al 2014).…”
Section: Introductionmentioning
confidence: 99%